The ambivalent role of high-frequency trading in turbulent market periods - Nikolaus Hautsch; Michael Noé; S. Sarah Zhang (Goethe University Frankfurt, Center for Financial Studies (CFS), 2017)
We show an ambivalent role of high-frequency traders (HFTs) in the Eurex Bund Futures market around high-impact macroeconomic announcements and extreme events. Around macroeconomic announcements, HFTs serve as market makers, post competitive spreads, and earn most of their profits through liquidity supply. Right before the announcement, however, HFTs significantly widen spreads and cause a rapid but short-lived drying-out of liquidity. In turbulent periods, such as after the U.K. Brexit announcement, HFTs shift their focus from market making activities to aggressive (but not necessarily profitable) directional strategies. Then, HFT activity becomes dominant and market quality can degrade.
urn:nbn:de:hebis:30:3-438666
Keywords: G10; G14; 330; High Frequency Trading; Market Making; News Releases; Futures Market; Brexit